Production of probiotic dark chocolate by alginate-chitosan microcapsules containing protective yeast with potent anti-Salmonella activity - Sara Shahryari; Alireza Sadeghi; Maryam Ebrahimi; Delasa Rahimi; Seid Mahdi Jafari (Carbohydrate Polymer Technologies and Applications)
Application of encapsulated probiotics in complex food matrices is a promising way to improve their viability and targeted delivery. In the present study, sequencing results of the PCR products led to the identification of Pichia kudriavzevii as the selected yeast isolate (YI) with high thermo-osmotolerance ability and low survival under simulated gastrointestinal (SGI) conditions. The inhibitory effect of YI on Salmonella enterica was also significantly (p < 0.05) higher than that of the other foodborne bacteria tested. Furthermore, viable and heat-killed cells of YI, as well as its cell-free supernatant reduced ochratoxin A by 35.28, 59.67 and 24.39 %, respectively according to the results of the HPLC-based assay. Moreover, field emission scanning electron microscopy and Fourier transform infrared analyses approved proper encapsulation of YI in alginate-chitosan (Alg-Ch). Survivability of encapsulated yeast under SGI conditions, before and after application in the produced dark chocolate was significantly higher than the free cells. In situ inhibitory activity of encapsulated yeast against S. enterica was also verified compared to the free yeast and free Ch during storage period of the product. Accordingly, the encapsulated yeast can be used as a proper biological preservative in processing of clean-label PRO chocolate.